Congenital Umbilical Cord Hernia: Prenatal and Postnatal Management - Rodriguez, Stephanie; Marty, Daisy; Folga, Barbara; Alrahmani, Layan (American Journal of Perinatology Reports, 2024)
Congenital umbilical cord hernia is often misdiagnosed and easily confused with a small omphalocele. It is different from postnatally diagnosed umbilical hernias and is believed to arise from persistent physiological mid-gut herniation. Its incidence is estimated to be 1 in 5,000, although some articles reported the incidence rate of approximately 0.2%. It is very important to clearly diagnose these cases in the antenatal period so that the patients receive appropriate management postnatally and to decrease the stress in the parents as well. Umbilical cord hernias have not been associated with other chromosomal anomalies.In this article, we describe a case of a patient who was diagnosed with an umbilical cord mass for which the course prenatally and postnatally was uncomplicated. It is very important to avoid misdiagnosing these cases, so that patients are appropriately treated in the postnatal course and to prevent complications such as bowel injury during cord clamping.
Keywords: umbilical cord hernia; maternal; omphalocele; ultrasound